Impact of Entrepreneurial Orientation Dimensions-Innovation, proactiveness and Risk-taking on Social Performance of Small and Medium Enterprises: Does Charismatic Leadership Moderate These Relationships? - Al-Dhobee, Yahya Ali; Goail, Majed; Al-Dhobee, Safwan (International Review of Management and Marketing, 2025)
Most studies on entrepreneurial orientation (EO) have examined its effects on financial performance, leaving a gap in understanding EO’s dimensions and their impact on SMEs’ social performance, particularly in developing economies. Additionally, the moderating role of charismatic leadership (CHL) on the EO-social performance (SOP) relationship remains underexplored. This study, based on the resource-based view theory and employing a multidimensional EO approach, investigates how the dimensions of EO—innovation (INNOV), proactiveness (PROA), and risk-taking (RIS) influence SOP, examining the moderating effects of CHL in manufacturing SMEs in Yemen. An analysis of data from 200 manufacturing SMEs was conducted using partial least squares (PLS) to test the hypotheses. The results reveal that PROA significantly enhances SOP, with CHL moderating this relationship, while INNOV and RIS do not significantly impact SOP, and CHL has no moderating effect on these dimensions. This study contributes to EO literature by examining EO through a multidimensional lens, highlighting its implications for SOP within SMEs, particularly in developing countries, and introducing CHL as a novel moderator. Practically, the findings suggest that manufacturing SME owners and managers should recognize that not all EO dimensions benefit social performance and that CHL can enhance social outcomes.